Bactericidal Effect of Photodynamic Therapy, Alone or in Combination with Mupirocin or Linezolid, on Staphylococcus aureus - Pérez-Laguna, Vanesa; Pérez-Artiaga, Luna; Lampaya-Pérez, Verónica; García-Luque, Isabel; Ballesta, Sofía; Nonell, Santi; Paz-Cristobal, Manuel P.; Gilaberte, Yolanda; Rezusta, Antonio (Frontiers in Microbiology, 2017)
Antibiotic treatments frequently fail due to the development of antibiotic resistance, underscoring the need for new treatment strategies. Antimicrobial photodynamic therapy (aPDT) could constitute an alternative therapy. In bacterial suspensions of Staphylococcus aureus, which is commonly implicated in cutaneous and mucosal infections, we evaluated the in vitro efficacy of aPDT, using the photosensitizing agents rose bengal (RB) or methylene blue (MB), alone or combined with the antibiotics mupirocin (MU) or linezolid (LN). RB or MB, at concentrations ranging from 0.03 to 10 μg/ml, were added to S. aureus ATCC 29213 suspensions containing >107 cells/ml, in the absence or presence of MU or LN (1 or 10 μg/ml). Suspensions were irradiated with a white metal halide ( 420-700 nm) or light-emitting diode lamp ( 515 nm and  625 nm), and the number of viable bacteria quantified by counting colony-forming units (CFU) on blood agar. Addition of either antibiotic had no significant effect on the number of CFU/ml. By contrast, RB-aPDT and MB-aPDT effectively inactivated S. aureus, as evidenced by a 6 log10 reduction in bacterial growth. In the presence of MU or LN, the same 6 log10 reduction was observed in response to aPDT, but was achieved using significantly lower concentrations of the photosensitizers RB or MB. In conclusion, the combination of MU or LN and RB/MB-aPDT appears to exert a synergistic bactericidal effect against S. aureus in vitro.